Dietary Carbohydrates Impair Healthspan and Promote Mortality - Ravichandran, Meenakshi; Grandl, Gerald; Ristow, Michael (Cell metabolism, 2017)
The prospective cohort study, named PURE, found that in >135,000 participants from 18 countries, nutritive carbohydrates increase human mortality, whereas dietary fat reduces it, requesting a fundamental change of current nutritional guidelines. Experimental evidence from animal models provides synergizing mechanistic concepts as well as pharmacological options to mimic low-carb or ketogenic diets. The prospective cohort study, named PURE, found that in >135,000 participants from 18 countries, nutritive carbohydrates increase human mortality, whereas dietary fat reduces it, requesting a fundamental change of current nutritional guidelines. Experimental evidence from animal models provides synergizing mechanistic concepts as well as pharmacological options to mimic low-carb or ketogenic diets.